Afghanistan’s Displaced People : A Socio-Economic Profile, 2013-2014 - Yde-Jensen, Thea; Krishnan, Nandini; Tan, Xiayun; Wieser, Christina (World Bank, Washington, DC, 2018)
Afghans represent the world’s largest protracted refugee population, and one of the largest populations to be repatriated to their country of origin in this century. Between 2002 and 2016, over six million refugees returned to Afghanistan from neighboring countries. In 2016 alone, returnees numbered more than a million. In an already difficult context, large-scale internal displacement and return from outside have strained the delivery of public services in Afghanistan and increased competition for scarce economic opportunities, not only for the displaced, but for the population at large. This note aims at contributing to our understanding of displacement in Afghanistan by comparing the socioeconomic profiles of three populations: (i) former refugees who returned to Afghanistan between 2002 and 2014 (“pre-2015 returnees”); (ii) internally displaced persons (“IDPs”); and (iii) non-displaced persons (“hosts”). The note captures and compares these groups’ situations at a specific time-point, using data from the 2013-14 Afghanistan Living Conditions Survey (ALCS). Importantly, the results document socioeconomic conditions just prior to the transfer of security responsibilities from international troops to the Afghan National Security Forces (ANSF) in 2014, which was associated with a subsequent decline in aid, both security and civilian, and a sharp drop in economic activity. The results presented here cover the largest return of Afghans to the county following the fall of the Taliban in 2002, but precede the more recent large-scale return of Afghan refugees from Pakistan in 2016-17. Future publications will extend the findings summarized here with analysis of new and existing data covering this recent influx. This research is part of an ongoing effort to document population displacement challenges and solutions in Afghanistan over time. Data from ALCS 2013-14 establish baseline socio-economic profiles for returned refugees, IDPs, and non-displaced hosts. Further research and analysis now in progress will document how these conditions have changed since 2013-14, and will distill evidence for policy to improve socio-economic outcomes among Afghanistan’s displaced and non-displaced people.